Strengthening The Halal Value Chain as A Strategy To Make Indonesia the Center of The Sharia Economy in The World - Natsir, Imron; Utami, Eva Yuniarti; Laksono, Muflih Adi; Indriastiningsih, Erna; Munizu, Musran (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is qualitative research with an exploratory approach. The data used in this research is secondary data that researchers obtained from books, scientific articles and other sources commonly used in every research. The data is collected first, then selected which ones best suit the theme of this article, and finally the data is analyzed and conclusions are drawn. The result in this article show the Halal Value Chain can be effective and become its own strength if implemented in the Unitary State of the Republic of Indonesia due to two things, namely first, Indonesia is the country with the first largest Muslim population in the world. Second, Indonesia has a lot of potential, especially in the food sector. Indonesia has 15 types of the most delicious food in the world which are of course halal.